Identity Questioning: Antecedents and Consequences of Prejudice Attributions. (22nd April 2019) - Albuja, Analia F.; Sanchez, Diana T.; Gaither, Sarah E.
Abstract: Many ethnic minorities in the United States hold both an ethnic minority and national American identity. Yet, they often encounter identity questioning when asked questions such as, "Where are you really from?, " which may operate as an ambiguous threat to their national identity. Because varied motivations (curiosity versus exclusion) create ambiguity, targets likely vary in their tendency to view identity questioning as prejudicial. Study 1 examined the extent to which ethnic minorities attribute identity questioning to prejudice, and the associated well‐being consequences. Study 2 examined the immigration policy‐oriented antecedents of identity questioning prejudice attributions. The results suggest that prejudice attributions are psychologically harmful (Study 1) and are associated with anti‐immigration policies (Study 2). Because identity questioning challenges one's ability to maintain a dual identity, it is important to better understand identity questioning. Specifically, these findings provide initial evidence of the role policy contexts may play in shaping identity questioning attributions.